Adesão ao tratamento medicamentoso por pacientes com hipertensão : influência de uso de um aplicativo m-Health - Mikulski, Bruna Spiller (2022)
Systemic Arterial Hypertension (SAH) is an important public health problem, which can be avoided because it is related to behavioral risk factors that are common and preventable. Low adherence to treatment continues to be one of the difficulties to the disease control. The m-Health applications can help in the monitoring of SAH, in addition to reinforcing adherence to drug therapy. The objective of this study was to investigate whether the use of an m-Health application by patient with SAH favors adherence to drug treatment and, consequently, the reduction/stabilization of BP. This is a non-randomized, controlled and non-blind clinical trial with 63 adult and elderly participants, men and women, aged between 28 and 92 years, diagnosed with SAH, and with accompaniment at UBS in the city of Passo Fundo, RS, Brazil. The sample was stratified into two groups: Intervention Group (IG), which used the MonitoraPA application for 3 months, and the Control Group (CG), which maintained the usual treatment. The assessment took place before and after the intervention. The instruments used were Mini Mental State Examination (MMSE), Sociodemographic Questionnaire, MBG Questionnaire and ARMS Questionnaire. Blood pressure measurements of the groups were performed before and after the intervention. Data were analyzed by SPSS 22.0 statistical software. The significance level was 5%. Comparing adherence to treatment between the control and intervention groups, both by the ARMS test and by the MBG test, there was no significant association between the groups. Regarding BP values, there was no significant difference between the pre and post-intervention groups, but there was a tendency to decrease the BP in the intervention group. These results provide subsidies to expand the use of health technologies in a multiprofessional perspective and with the accompaniment of health professionals from the UBS, since they showed signs of a reduction in the BP. The results are presented in Scientific Production I, which will later be submitted to a journal in the area.